PENDUDUK PRIBUMI, PARIWISATA DAN PEMBANGUNAN BERKELANJUTAN DI DESA NEMBERALA KABUPATEN ROTE NDAO - yonce, frit elisa (Universitas Pendidikan Nasional, 2017)
ABSTRACTNemberala village located on the west coast of the island of Rote is a leading tourist area in Rote Ndao regency, East Nusa Tenggara province. Kabutan located at the southern tip of Indonesia is a new district carved out of Kupang district in 2002. Local Government Support to the development of this tourist area is absolutely necessary in the structuring of the region either short, medium and long conceptual. Since the area is known as one of the Tourism Destination Region (DTW) for potential sala surfing being one of the best in the world, tourism in the village looks more bergeliat Nemberala. Almost every day brings a lot of tourists that come and go in the village which has a pretty long beach with white sand is dazzling. Stretching the development of tourism industry in the village Nemberala can also be seen from the increasing number of foreign and local investors who have and are building support facilities, such as hotels and home stay that much built around the coastal area Nemberala.The problems raised in this study are: (1) how to make optimum use of the potential tourist attraction located in the tourist area Nemberala Beach Area; (2) how the benefits derived by indigenous communities in the development and keterlibatanya Nemberala Beach tourist area on an ongoing basis; and (3) how the stages in building Nemberala Beach tourist area. While the purpose of the implementation of this research are: (1) to identify potential tourist attraction Nemberala Coast and its management are best benefits for people in the tourist area around Nemberala; (2) to assess the extent to which local people have participated actively in the development of tourist areas Nemberala Beach; (3) know what the most appropriate strategy in the development of Nemberala Beach tourist area on an ongoing basis.The data used in this study is the combined data between qualitative and quantitative sample was taken purposively. Data have been collected and analyzed by descriptive qualitative SWOT analysis. Results of analysis addressing that beach tourist area Nemberala has various tourism potential should be developed as a tourist destination areas (DTW) and has met four (4) an important component in the tourism industry with a term of four 4A, the attraction (tourist attraction), accessibility (access to tourist areas), amenities (facilities and travel services), ancillary (institutional and human resources will support tourism), by way of implementing several strategies such as strategic SWOT SO, ST, WO and WT. It is hoped that this research will be able to make a positive contribution in planning development strategies Nemberala Coast tourist area in the future, the economic impact for the indigenous communities in a sustainable manner.Keywords: Sustainable Tourism, Community-Based Tourism